Accuracy of age Estimation Method Following the Length of Mandibular Body: A Cross-Sectional Study - Marvi Shaikh, Abdul Jabbar, Sana Shah, Syeda Sadia Hassan, Alvina Ali Shaikh, Hassan Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim is to identify the accuracy of age estimation following the mandibular body length by lateral cephalograms Methodology: Mandibular body length was calculated using lateral cephalograms. 60 participants’ lateral cephalograms were traced using the same view box. LMB was obtained by marking reference points on the most anteroinferior part of the mandible, specifically the gonion (Go), which is the constructed point at the intersection of the ramus plane and the mandibular plane, and the gnathion (Gn), which is the constructed point between the menton and the pogonion. With a ruler, the line drawn from Go to Gn was measured, and the results were recorded in millimeters. The results of the acquired values were statistically analyzed Result: With all these parameters (P >0.9516 mandibular body length the findings obtained are of no important distinction between estimated age and real age. The duration of the mandibular body indicates less normal error test (i.e. 0.188) among these. Practical implication Conclusion: mandibular body length was not statistically significant with the chronological age of the patient. The mandibular body length, however, is the highest parameter with the least standard error. Little difference was seen with LMB in this study, with a P value of 0.0490. The mean and standard deviation of the mean length of the mandibular body in males and females from lateral cephalogram showed insignificant results with the p-value. Keywords: lateral cephalogram, Mandibular measurements, and Orthopantomograms.